Foursquare and the Parochialization of Public Space - Humphreys, Lee; Liao, Tony (AoIR Selected Papers of Internet Research, 2013)
The mobile social network Foursquare has gained popularity in the last few years among both users and businesses. This article explores how the use of Foursquare changes and impacts people’s sense of place. Drawing on the work of Lofland (1998) on the social production of space, we argue that as new socio-spatial information (i.e. who checks in where) is introduced via the mobile social network, it can change the way people experience a place. Based on qualitative in-depth interviews with active Foursquare users, we explore person-to-person and person-to-place connections and argue that Foursquare promotes parochialization of public space.